A DMAIRC approach to lead time reduction in an aerospace engine assembly process. Issue 1 (2014) - ,; ,; ,; ,; ,
<x xml:space="preserve">Abstract</x> Purpose – Problem solving and continuous process improvement are key elements to achieve business excellence. Many problem solving and process improvement methodologies have been proposed and adopted by organisations, with DMAIC being the most widely used. The purpose of this paper is to present an empirical application of a modified version of DMAIC which enabled a world‐class organisation to achieve an optimum reduction in the lead time of its aerospace engine assembly process. Design/methodology/approach – The paper reviews the most commonly used problem solving and process improvement methodologies and specifically, DMAIC, its variations and limitations. Based on this, it presents define, measure, analyse, improve, review, control (DMAIRC). Finally, DMAIRC is empirically applied through a case study, in a world‐class manufacturing organisation. Findings – The results obtained from the case study indicate that DMAIRC is an effective alternative to achieve the maximum improvement potential of a process. In particular, DMAIRC helped the organisation studied to achieve a 30 percent reduction in the lead time of its engine assembly process. Originality/value – The novel problem solving and process improvement methodology presented in this paper can be used by organisations to undertake a more effective improvement project by assuring that the maximum potential of their improvement initiatives and processes is achieved.